GEOGRAPHIC INFORMATION SYSTEMS DESIGN OF TOURIST ATTRACTION AND NEAREST FACILITY IN BANDAR LAMPUNG CITY - Rani, Devi Kathina; -, Yulmaini (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Tourism is one of the selling point that BandarLampung City has. The information about the location oftourist attraction and the supporting facility was given inbooklet and tourism map. The information distributionthrough those media havenât use the technology thatappropriate to the current development.Some research methods were used in thisresearch such as, data collection methods and systemdesign methods. The data collection methods were donein several ways such as interview with the respondents,literature study and observation. The system designmethods use UML (Unified Modelling Language).The output from this research is a design ofgeographic information system that interactive with theuser and able to attract the tourist attention to visit BandarLampung City and the tourist attraction. With this designhopefully can bring more information about a touristattraction in Bandar Lampung City and gain more touristto visit Bandar Lampung City.KEY WORDS: Geographic Information System, Design, Tourism